Breathing variability and brainstem serotonergic loss in a genetic model of multiple system atrophy. Issue 3 (17th January 2014) - Flabeau, Olivier; Meissner, Wassilios G.; Ozier, Annaig; Berger, Patrick; Tison, François; Fernagut, Pierre‐Olivier
ABSTRACT: Breathing disorders like sleep apnea, stridor, and dysrythmic breathing are frequent in patients with multiple system atrophy (MSA). These observations have been related to neurodegeneration in several pontomedullary respiratory nuclei and may explain the occurrence of sudden death. In this study, we sought to determine whether these functional and neuropathological characteristics could be replicated in a transgenic model of MSA. Mice expressing human wild‐type α‐synuclein under the control of the proteolipid promoter (PLP‐αSYN) were compared with age‐matched controls. Using whole‐body, unrestrained plethysmography, the following breathing parameters were measured: inspiratory and expiratory times, tidal volume, expiratory volume, peak inspiratory and expiratory flows, and respiratory frequency. For each category, the mean, coefficient of variation, and irregularity score were analyzed. Brains were then processed for stereological cell counts of pontomedullary respiratory nuclei. A significant increase in the coefficient of variation and irregularity score was observed for inspiratory time, tidal volume, and expiratory volume in PLP‐αSYN mice ( P  < 0.05). Glial cytoplasmic inclusions were found in the medullary raphe of PLP‐αSYN mice, together with a loss of serotonergic immunoreactivity in the raphe obscurus ( P  < 0.001) and pallidus ( P  < 0.01). There was a negative correlation between α‐synuclein burden and raphe pallidus cell counts ( P  < 0.05). There was no significant neuronal loss in the pre‐Botzinger complex. The PLP‐αSYN mouse model replicates the breathing variability and part of the neuronal depletion in pontomedullary respiratory nuclei observed in patients with MSA. Our findings support the use of this model for future candidate drugs in the breathing disorders observed in MSA. © 2014 International Parkinson and Movement Disorder Society